2022
DOI: 10.1186/s12877-022-03416-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and motor correlates of frailty: dissociation between frailty phenotype and frailty index

Abstract: Background: Frailty has been associated with a decline in sensory and motor function. However, given that different frailty measures were shown to overlap but also differ in their diagnostic properties, sensory and motor correlates of frailty might be different depending on the operationalization of frailty. Our objective was to identify sensory and motor determinants of frailty and compare the results between frailty phenotype (FP) and frailty index (FI).Methods: Data from 44 pre-frail and frail subjects aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Hearing loss often associated with frailty and may warrant measuring clinically. Beier, et al (2022) [80] examined two different assessments of frailty. They determined that the Frailty Index (FI) is more sensitive to hearing loss while the Frailty Phenotype (FP) results are only associated with motor function.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hearing loss often associated with frailty and may warrant measuring clinically. Beier, et al (2022) [80] examined two different assessments of frailty. They determined that the Frailty Index (FI) is more sensitive to hearing loss while the Frailty Phenotype (FP) results are only associated with motor function.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…The FI is calculated by dividing the number of deficits present by the total possible number of deficits (40). Scores exceeding 0.25 (10 deficits) are considered to indicate frailty [80]. The authors emphasize that hearing loss should be included in frailty assessments (using the FI) given their findings and considering previous described association between hearing loss and cognition, gait-speed, fall-risk, depression, hospitalization and mortality.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Another study found moderate agreement between the FP and the FI in finding the same frail persons. 31 Furthermore, authors discuss that discordant identification could be related to the measures’ capacity in capturing sensory, motor and psychological impairment. 31 A recent study of the CFS and an electronic FI found substantial heterogeneity between the measures and low support for convergent validity.…”
Section: Introductionmentioning
confidence: 99%
“… 31 Furthermore, authors discuss that discordant identification could be related to the measures’ capacity in capturing sensory, motor and psychological impairment. 31 A recent study of the CFS and an electronic FI found substantial heterogeneity between the measures and low support for convergent validity. 32 Assessment of frailty increased during the COVID-19 pandemic since it was found to be a useful way to determine risk for adverse outcomes and prognosis of older patients with COVID-19 in the acute care setting.…”
Section: Introductionmentioning
confidence: 99%